Myocardial infarction - Elder, Annemarie N.; Blanchard & Loeb Publishers ([?] : Blanchard & Loeb Publishers, 2000)
(Producer) Practical information on every clinically relevant aspect of myocardial infarction. Shows what's happening inside the patients body and what it means for nursing care before, during, and after an MI
Keywords: Myocardial Infarction -- nursing; Myocardial Infarction -- physiopathology